Oxidative Stress-Related lncRNAs Are Potential Biomarkers for Predicting Prognosis and Immune Responses in Patients With LUAD - Sun, Xinti; Huang, Xingqi; Sun, Xiaojuan; Chen, Si; Zhang, Zeyang; Yu, Yao; Zhang, Peng (Frontiers in Genetics, 2022)
Lung adenocarcinoma, as cancer with an extremely poor prognosis and insensitive to chemotherapy, is increasingly harmful to society and individuals. Previous studies have demonstrated that oxidative stress and lncRNAs play a vital role in many biological processes. Therefore, we explored the role of lncRNAs associated with oxidative stress in the prognosis and survival of LUAD patients. We examined the expression profiles of lncRNAs and oxidative stress genes in this study, and a prognosis prediction model, as well as a nomogram, were built based on oxidative stress-related lncRNAs. Functional analysis and drug sensitivity analysis depending on oxidative stress-related lncRNAs signature were performed as well. Moreover, we investigated the relationship between immune response and immunotherapy. Results showed that a risk scoring model based on 16 key oxidative stress lncRNAs was able to distinguish the clinical status of LUAD and better predict the prognosis and survival. Additionally, the model demonstrated a close correlation with the tumor immune system, and these key lncRNAs also revealed the relationship between LUAD and chemotherapeutic drug sensitivity. All of our work aims to provide new perspectives and new ideas for the treatment and management of LUAD.